Predicting self-evacuation in Australian bushfire. (15th March 2019) - Strahan, Kenneth William; Whittaker, Joshua; Handmer, John
ABSTRACT: Australian bushfire safety policy does not require mandatory evacuation from bushfire as practiced in North America and other jurisdictions. Australian householders confronted with a bushfire threat must decide whether they remain and defend their property or evacuate. A better understanding of factors that influence householders' decisions to self-evacuate can inform bushfire safety policy. Studies have identified variables that motivate evacuation from various hazards, including wildfire, but factors shaping the decision processes are not well understood. The Protective Action Decision Model (PADM) provided a theoretical framework of factors influencing protective response to hazard to analyse the actions of householders affected by two bushfires. Three factors that predict self-evacuation were identified: the perception that evacuation is effective in protecting personal safety; the receipt of official warnings; and perceived threat to property. These findings reinforce the importance of increasing householder awareness and sensitivity to the danger posed by bushfire; the adequacy of people's bushfire preparedness; the effectiveness of early evacuation in protecting personal safety; and the potential persuasiveness of accurate, relevant and timely official warning messages in influencing safe evacuation from bushfire.